2019
DOI: 10.1007/s00170-019-03937-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining kinetic energy distribution of the working medium in a centrifugal disc finishing process—part 2: experimental analysis with the use of acoustic emission signal

Abstract: This paper addresses the problem of estimating the kinetic energy distribution of the working medium in a centrifugal disc finishing process. Centrifugal disc finishing is a highly effective way of finishing surfaces, especially in the case of complex shapes, made from a variety of materials. The process is, however, frequently very time-consuming. The identification method of a region with a high kinetic energy potential by measurement of acoustic emission signal is described and verified by surface roughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In the companion paper [1], the experimental tests were developed to verify the results of simulation tests, to carry out experiments of the actual centrifugal disc finishing process using the AE signal and to compare the results of simulation and experimental tests.…”
Section: Conclusion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…In the companion paper [1], the experimental tests were developed to verify the results of simulation tests, to carry out experiments of the actual centrifugal disc finishing process using the AE signal and to compare the results of simulation and experimental tests.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…This paper and its companion [1] describe numerical and experimental methods aimed at determining the kinetic energy distribution of the working medium in the centrifugal disc finishing process. Surface machining in centrifugal disc finishing, using a working medium in the form of abrasive particles, is an effective way of polishing the surfaces of objects with complex shapes and diverse dimensions made from a variety of materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as the research carried out at the Department of Production Engineering has shown, there is a differentiation of the energy distribution of the working charge in its shaped spatial structure at a given rotational speed [1,2] (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The paths of movement of the abrasive media in the working container of the disc centrifugal machine [1, The paths of movement of the abrasive media in the working container of the disc centrifugal machine[1,2] …”
mentioning
confidence: 99%